Urban–rural disparities in minimum acceptable diet intake among children aged 6–23 months in Ethiopia: A multivariable Decomposition analysis of Ethiopian demographic and health survey 2019 - Mohammed, Anissa; Tareke, Abiyu Abadi; Keleb, Awoke; Kebede, Natnael; Tsega, Yawkal; Endawkie, Abel; Kebede, Shimels Derso; Mesfin Abera, Kaleab; Tilahun Abeje, Eyob; Bekele Enyew, Ermias; Daba, Chala; Asmare, Lakew; et al. (Frontiers in Public Health, 2024)
The achievement of the minimum acceptable diet intake (MAD) stands at 14% among urban and 10% among rural under five children in Ethiopia. Consequently, identifying the determinants of the urban-rural gap is vital for advancing Sustainable Development Goals (SDGs), fostering healthier communities, and developing evidence-driven approaches to enhance health outcomes and address disparities.Objective: To decompose the urban-rural disparities in minimum acceptable diet intake in Ethiopia using Ethiopian Mini-Demographic and Health Survey 2019 data.The study was conducted using Ethiopian Demographic and health survey 2019 report.We have included 1496 weighted children aged 6-23 months with stratified sampling technique.The main outcome variable minimum acceptable diet was calculated as a combined proportion of minimum dietary diversity and minimum meal frequency. A decomposition analysis was used to respectively between urban and rural residents with coefficients (β =-0.002, 95%CI: -.003 –0.0011) and (β =-30.7, 95%CI: -0.025 –0.0085). From the effect coefficients, effect of institutional delivery was responsible for 1.99% widening of the gap between urban and rural residents in minimum acceptable diet intake (β=-0.0862, 95%CI: -0.1711–.0012).There is a significant variation between urban and rural residents in minimum acceptable diet. The larger portion of discrepancy was explained by endowment effect.Educational status of mothers with college and above, parity, age of child and place of delivery were the significant factors for the discrepancy of minimum acceptable diet intake in urban and rural residents